Risk Management Analysis in the Implementation of the Mataram Mayor's Office Development Project - Anang Aprillah; Ngudiyono Ngudiyono; Made Mahendra (Green Publisher Indonesia, 2026)
In the implementation of construction projects, particularly the Mataram Mayor's Office Development Project, various risks may lead to cost overruns, delays in project completion, and reduced work quality. During the construction phase, contractors face various uncertainties; therefore, effective risk management is required. This study aims to identify risk sources, conduct risk assessments, and formulate risk mitigation strategies. The method employed in this study is the Risk Breakdown Structure (RBS) for risk identification and the AS/NZS 4360:2004 standard for determining risk levels and categories. The identification results revealed that 44 risk variables were identified in the project. Following the risk assessment, 6 risks were categorized as high risk, 30 risks as medium risk, and 8 risks as low risk. Risk management strategies are implemented through monitoring and supervision to strengthen supply chains, manage logistics, and ensure preparedness in addressing uncertainties such as delays and material shortages. Furthermore, improving work culture, implementing Occupational Health and Safety Management (OHSM), applying systematic change management, enhancing effective communication, and developing adaptive weather planning are key measures to minimize risks and maintain project continuity.